Comparing bacterial dynamics for the conversion of organics and humus components during manure composting from different sources - Li, Yan; Li, Jun; Chang, Yuan; Li, Ruoqi; Zhou, Kaiyun; Zhan, Yabin; Wei, Renyue; Wei, Yuquan (Frontiers in Microbiology, 2023)
The study aimed to compare the differences in organic fractions transformation, humus components and bacterial community dynamics during manure composting from different sources, and to identify the key biotic and abiotic factors driving the humification process. Five types of manure [pig manure (PM), cow dung (CD), sheep manure (SM), chicken manure (CM) and duck manure (DM)] were used as raw materials for 30-day composting. The results showed the obvious difference of organic fractions decomposition with more cellulose degradation in CD and SM composting and more hemicellulose degradation in PM and CM composting.Composting of PM and CD contained significantly higher humus fractions than the other composts. Fluorescence spectra indicated that SM composting tended to form structurally stable humic acid fractions, while CM and DM tended to form structurally complex fulvic acid fractions. Pearson correlation analysis showed that humification process of composts in category A (PM, CD) with higher humification degree than category B (SM, CM, DM) was positively correlated with lignin and hemicellulose degradation. Bioinformatics analysis found that Lysinibacillus promoted the degradation of hemicellulose and the conversion of fulvic to humic acid in the composts of category A, and in category B, Thermobifida, Lactobacillus, and Ureibacillus were key genera for humic acid formation. Network analysis indicated that bacterial interaction patterns had obvious differences in composting with different humus and humification levels.